Medieval Britain and Ireland in 2017 - Webley, R; Rogerson, A; Ashley, S (Taylor and Francis, 2018)
This section of the journal comprises two core sets of reports linked to work in 2017: finds and analyses relating to the Portable Antiquities Scheme (PAS) and site-specific discoveries and reports in medieval Britain and Ireland (MB&I;), with a selection of highlighted projects. For the PAS report, reviews on coin and non-coin finds and on specific research angles are presented. For MB&I;, the Society is most grateful to all contributors (of field units, museums, universities, developers, specialist groups and individuals) who have provided reports on finds, excavations, field-surveys and building analyses for 2017. For MB&I;, see below for the format and content of the Fieldwork Highlights section and for contact details of the compilers. Annual Specialist Groups Reports appear in the Society’s Newsletter.